2021
DOI: 10.1101/2021.12.22.21268237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal trends in hospitalizations and 30-day mortality in older patients during the COVID pandemic from March 2020 to July 2021

Abstract: Importance: Previous reports have suggested reductions in mortality risk from COVID-19 throughout the first wave of the COVID-19 pandemic. Mortality changes later in the pandemic and pandemic effects on other types of geriatric hospitalizations are less studied. Objectives: To describe the changes in hospitalizations and 30-day mortality in Stockholm for patients 70+ receiving inpatient geriatric care for COVID-19 and other causes. Design: Observational study. For patients 70 or older, we present the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It also assumes the relatively younger Stockholm demographics rather than the national one, and is therefore an underestimate of the national IFR. A later Sweden-wide IFR estimate of 0.76% [0.65, 0.87] was published in November 2020 [45] and aligns well with our estimate above. Although our 95% CrI is comparatively wide, this is partially due to modeling each period independently and without any regularization in the transition between periods.…”
Section: Marginal Riskssupporting
confidence: 90%
See 2 more Smart Citations
“…It also assumes the relatively younger Stockholm demographics rather than the national one, and is therefore an underestimate of the national IFR. A later Sweden-wide IFR estimate of 0.76% [0.65, 0.87] was published in November 2020 [45] and aligns well with our estimate above. Although our 95% CrI is comparatively wide, this is partially due to modeling each period independently and without any regularization in the transition between periods.…”
Section: Marginal Riskssupporting
confidence: 90%
“…The first two entries in the table overlap the estimates from [46]: Nov 2020 = [0.60, 1.46]%, and Jan 2021 = [0.56, 1.44]%. Clearly, the IFR was trending downwards and this is also known to be the case in Stockholm [45] as well as for the world in general [46]. Of interest is also the case fatality risk (CFR) [47], i.e., the risk of death conditioned on being diagnosed with the disease.…”
Section: Marginal Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a surge in admissions to the included clinics during the Omicron wave, yet we noticed a significantly lower mortality rate in that period compared to previous waves, which is consistent with recent studies suggesting a decreased disease severity of the Omicron variant [ 16 , 17 ]. Interestingly, patients admitted during the 1st, 2nd, and Omicron waves were older and frailer than those admitted during the 3rd wave in 2021, which may in part be explained by the more stringent selection of admissions during periods of high community spread of COVID-19, leading to a sicker, older, and frailer patient group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the Swedish eFI is associated with adverse outcomes in several geriatric patient groups (e.g., fragility fracture, congestive heart failure, dementia), but it is less clear if the eFI has similar utility in COVID-19 patients. Compared to regular geriatric patients who generally have lower and more stable mortality rates over time, CO-VID-19 patients admitted to geriatric hospitals in Sweden represent a different patient group, who typically have 398 DOI: 10.1159/000527206 higher mortality rates, younger age, and longer lengths of stay [32,33]. The primary aim of this study was to assess the association between the Swedish eFI and adverse outcomes (mortality, readmission, and length of stay) in hospitalized older COVID-19 patients across the pandemic waves.…”
Section: Introductionmentioning
confidence: 99%